Energy particle-physics : the efforts of Abdel Nasser Tawfic - Abdulwaheed, Musa; Ismail, Ahmad Faris (IIUM Press, 2011)
Particle physics kas impacted the philosophy of science greatly. It is a branch of physics that studies the existence and interactions of particles that are the constituents of what is usually referred to as matter or radiation. Abdel Nasser Tawfik, Egyptian-born German particle physicist has made his mark in this field. He has the award of Who's Who in Science and Engineering and aims at simplifying scientific issues for public and fmding nexus between science and religion. Dr. Tawfik has been providing seminars on various scientific issues. The objective of this chapter is to discuss his contribution to energy particle specifically in the area of Quantum Chromo-Dynamics (QCD). It is of note that the significance of this chapter is appreciating efforts of Islamic Thinkers and Scientists like Tawfik and his QCD phase diagram contribution to the field of energy particlephysics. The method ofresearch adopted is based on library materials, internet sources and academic discussions. The theory and the research framework are limited to focusing mainly on reviewing the person of Abdel Nasser Tawfik, energy particle physics and the Tawfik's outstanding contribution